Prediction of CD8+ T cell infiltration in the tumor microenvironment of HGSOC patients - Jia Mai; Ling Yang; YuXin Chen; XiaoXu Zeng; HongJian Xie; XiaoJuan Liu (Scientific Reports)
Abstract The tumor microenvironment (TME), particularly CD8+ T cell infiltration, critically influences high-grade serous ovarian cancer (HGSOC) progression and treatment response. The development and management of cancer depend heavily on CD8+ T cells. Identifying non-invasive predictors of TME immune status is crucial. We investigated whether clinicopathologic characteristics and peripheral blood parameters could predict CD8+ T infiltration in TME of HGSOC. Two independent cohort were analyzed: (1) A multicenter tissue microarray (TMA) cohort of 105 epithelial ovarian cancer cases revealed that high CD8+ T cell density in tumor parenchyma, stroma, or whole tissue was significantly associated with good prognosis. (2) A retrospective cohort of 95 HGSOC patients from West China Second University Hospital (2016–2020) demonstrated that peripheral blood lymphocytes, globulin (GLB), lactate dehydrogenase (LDH), and low-density lipoprotein (LDL) correlated with CD8+ T cell infiltration in TME. These findings support non-invasive blood markers as predictors of tumor immune status and highlight chemotherapy’s role in enhancing CD8+ T cell recruitment.